Effects of febrile and afebrile seizures on oxidant state in children - Akarsu, Saadet; Yilmaz, Seval; Ozan, Sema; Kurt, Abdullah; Benzer, Fulya; Gurgoze, M. Kaya (Elsevier Science Inc, 2007)
No comparative studies have addressed the oxidant and antioxidant states of blood and cerebrospinal fluid. To reveal this differential state, the study was designed to identify the seizure type with the worse prognosis by determining erythrocyte arginase and erythrocyte catalase, plasma and cerebrospinal fluid malondialdehyde, and plasma and cerebrospinal fluid nitric oxide levels. Study groups were classified as febrile (group 1, n = 21), afebrile (group 2, n = 21), and control (group 3, In = 41, subdivided as 3a, febris positive, convulsion negative, and 3b, febris negative, convulsion negative). Levels of erythrocyte arginase, erythrocyte catalase, plasma malondialdehyde, cerebrospinal fluid malondialdehyde, plasma nitric oxide, and cerebrospinal fluid nitric oxide levels were determined for all groups. A difference was detected between the control and febrile seizure groups with respect to erythrocyte catalase and plasma and cerebrospinal fluid levels of nitric oxide (P < 0.05). Both febrile states and convulsions influence oxidative mechanism. Oxidative stress-generating potential differs for febrile and afebrile seizures. In afebrile seizures, greater levels of oxidative stress might affect prognosis adversely. This phenomenon can be interpreted in terms of fever as a protective factor against possible neurological damage during convulsive seizures. (C) 2007 by Elsevier Inc. All rights reserved.
Keywords: Nitric-Oxide; Oxidative Stress; Lipid-Peroxidation; Superoxide-Production; Rat-Brain; Arginine; Melatonin; Arginase; Anticonvulsant; Inhibition